Assessing the Impact of Tax Regulation Changes on Cross-Border E-Commerce: A Difference-In-Difference Approach - Siti Arifa'atus Sa'adah; Lilis Nurul Husna; Ramadhany Nugroho (Directorate General of Taxes, 2025)
Policy analysis is essential for evaluating and measuring the achievement of policy objectives. This study employs a differences-in-differences method to assess the impact of the implementation of Ministry of Finance Regulation No. 199/PMK.04/2019, which introduced a new tax policy on cross-border e-commerce. Using cross-border e-commerce data (consignment note documents) from 2017 to 2022 provided by the Directorate General of Customs and Excise, the study measures the policy’s effect on import values and the number of transactions (declared documents). The results show that the implementation of the new tax regulation in cross-border e-commerce has reduced importation values and the number of transactions. Furthermore, the tariff increases on fashion commodities, such as bag, shoes, clothes, resulted in a more significant reduction. These findings indicate that the implementation of this policy has succeeded in fulfilling its objectives of controlling importation, thereby providing greater protection to domestic producers through fair tax treatment and creating a level playing field.